AJARAN TASAWUF SULTAN AGUNG: KAJIAN ISI SERAT SASTRA GENDHING: MYSTICAL TEACHING OF SULTAN AGUNG: STUDY ON TEXT SERAT SASTRA GENDHING - Zaenuddin Zaenuddin (Penamas, 2014)
Substantially, the text of Serat Sastra Gendhing, written by Sultan Agung describes two disciplines in Islamic studies, the theology and mysticism/sufism. This study aims at exploring its Sufism aspect. Using hermeneutics method developed by Gadamer, this study found that Serat Sastra Gendhing teaches us about panetheism, where there two things are interrelated and interdependent. These two things are reflected in the relationship between the Creator and the creation. The Islamic mysticism in Serat Sastra Gendhing replicate the one of a famous mystic Ibn Arabia. The underlying of the text writing is that the King desire to transmit Islamic teaching to his people using Javanese culture approach. For today’s reader, the text is serat piwulang, which explains on how to establish a good communication to the Creator and to other creatures.Keywords: Serat Sastra Gendhing text, sufism, Sultan Agung, Javanese culture.Teks Serat Sastra Gendhing karya Sultan Agung secara substantif menjelaskan dua disiplin dalam ilmu keislaman, yakni ilmu teologi dan tasawuf. Penelitian ini bertujuan mengungkapkan aspek tasawuf dari teks tersebut. Penelitan ini menggunakan metode hermeneutika yang dikembangkan Gadamer. Penelitian ini menemukan, bahwa Serat Sastra Gendhing merupakan teks yang mengajarkan tentang pantheisme, di mana dua hal saling berkaitan dan saling membutuhkan, yang tergambar dalam hubungan antara Pencipta dan yang dicipta. Adapun corak mistik Islam dalam Serat Sastra Gendhing cenderung pada mistik Ibnu Arabi. Penulisan serat tersebut dilatarbelakangi oleh keinginan seorang raja untuk menyampaikan ajaran agama Islam kepada rakyatnya dengan menggunakan pendekatan budaya Jawa. Sedangkan untuk pembaca sekarang, serat tersebut merupakan serat piwulang agar manusia menjalin komunikasi yang baik dengan Sang Pencipta maupun dengan sesama makhluk ciptaan.Kata Kunci: Serat Sastra Gendhing, tasawuf, Sultan Agung, budaya Jawa.